Association between genetic variants and development of antibodies to infliximab: A cross-sectional study in Chinese patients with Crohn’s disease - Zhu, Kouzhu; Ding, Xiaoliang; Chen, Zhiyao; Xi, Qinhua; Pang, Xueqin; Chen, Weichang; Miao, Liyan (Frontiers in Pharmacology, 2023)
Aims: Genetic variants increase the susceptibility to anti-drug antibodies (ADA) in response to anti-TNF therapy in chronic inflammatory diseases. However, little is known about genetic variants in Chinese populations. This study aimed to identify genetic variants contributing to the risk of the development of antibodies to infliximab (ATI) in Chinese patients with Crohn’s disease (CD). Methods: CD patients (n = 104) treated with infliximab (IFX) during the maintenance therapy were enrolled in this cross-sectional study. ATI was assessed by an in-house developed drug-tolerant ELISA method. ATI titers of 1:20 and ≥1:60 were considered a low titer and a high titer, respectively. Thirteen types of single nucleotide polymorphisms (SNPs) within 13 genes involved in the immune process, the susceptibility to chronic inflammatory diseases, cytokines and apoptosis pathways were investigated. Results: The median trough levels of infliximab (TLI) in patients with clinical remission (CR) were higher than those in patients without CR (3.80 vs. 1.50 μg/mL, p < .001). The median TLI in patients with high-titer ATI was significantly lower than that in ATI-negative patients (1.15 vs. 4.48 μg/mL, p < .001) or those with low-titer ATI (1.15 vs. 2.95 μg/mL, p = .03). The HLA-DQA1*05 rs2097432 GG and GA genotypes were more frequent in patients with ATI (GG and AG vs. AA, 27/38 = 71.05% vs. 29/66 = 43.94%, OR 2.94, 95% CI 1.19–7.30, p = .02). Patients carrying the CC and AC genotypes of rs396991 in FCGR3A were associated with a higher frequency of ATI formation (CC and AC vs. AA, 37/57 = 64.91% vs. 19/47 = 40.43%, OR 2.94, 95% CI 1.24–6.96, p = .01). According to the number of variants in rs2097432 and rs393991, patients with two variants had a higher proportion of producing ATI (two variants vs. no variant, 17/21 = 80.95% vs. 9/30 = 30.00%, OR 9.92, 95% CI 2.59–37.87, p = .001; single variant vs. no variant, 30/53 = 56.60% vs. 9/30 = 30.00%, OR 3.04, 95% CI 1.18–7.88, p = .02). No association was found between other SNPs and ATI production. Conclusion: Rs2097432 in HLA-DQA1*05 and rs396991 in FCGR3A are associated with ATI production in Chinese patients with CD. A pharmacogenomic strategy could help with the clinical management of CD.